Effects of Sugar Cane Molasses Addition on the Fermentation Quality, Microbial Community, and Tastes of Alfalfa Silage - Runbo Luo; Yangdong Zhang; Fengen Wang; Kaizhen Liu; Guoxin Huang; Nan Zheng; Jiaqi Wang (Animals, 2021)
The objective was to study the effects of sugar cane molasses addition on the fermentation quality and tastes of alfalfa silage. Fresh alfalfa was ensiled with no additive (Control), 1% molasses (M1), 2% molasses (M2), and 3% molasses (M3) for 206 days. The chemical composition and fermentation characteristics of the alfalfa silages were determined, the microbial communities were described by 16S rRNA sequencing, and the tastes were evaluated using an electronic tongue sensing system. With the amount of added molasses (M), most nutrition (dry matter and crude protein) was preserved and water-soluble carbohydrates (WSC) were sufficiently used to promote the fermentation, resulting in a pH reduction from 5.16 to 4.48. The lactic acid (LA) content and LA/acetic acid (AA) significantly increased, indicating that the fermentation had turned to homofermentation. After ensiling, Enterococcus and Lactobacillus were the dominant genus in all treatments and the undesirable microbes were inhibited, resulting in lower propionic acid (PA), butyric acid (BA), and NH3-N production. In addition, bitterness, astringency, and sourness reflected tastes of alfalfa silage, while umami and sourness changed with the amount of added molasses. Therefore, molasses additive had improved the fermentation quality and tastes of alfalfa silage, and the M3 group obtained the ideal pH value (below 4.5) and the best condition for long-term preservation.